Cooperative Catalysis in Glycosidation Reactions with O‐Glycosyl Trichloroacetimidates as Glycosyl Donors1. Issue 38 (26th July 2013) - Geng, Yiqun; Kumar, Amit; Faidallah, Hassan M.; Albar, Hassan A.; Mhkalid, Ibrahim A.; Schmidt, Richard R.
<x xml:space="preserve">Abstract</x> Thiourea mediates cooperative glycosidation through hydrogen bonding. N, N′‐Diarylthiourea as cocatalyst enforces an SN2‐type acid‐catalyzed glycosidation even at room temperature (see scheme; Bn=benzyl). From O‐(α‐glycosyl) trichloroacetimidates as glycosyl donors and various acceptors, β‐glycosides are preferentially or exclusively obtained.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>